TRANSFORMASI BUDAYA MELALUI PEMBELAJARAN MATEMATIKA BERMAKNA DI SEKOLAH - Rohaeti, Euis Eti (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2011)
Abstract: One of many other functions of teaching at school level is as a means of cultural transformational process. Mathematics, one of the sciences resulted from human thoughts and activities, at school level is now expected to be more meaningful through the insertion of familiar concepts which are related to the local culture of the students. This cultural incorporation is then extended into national culture with its multicultural characteristics and global culture which is commonly cross-cultural based. Through this, it is hoped that culture can be applied and kept by our young generation through their way of thinking, viewing and doing things. All these can also increase their commitment to keep the cultural differences nation wide. Keywords: Cultural transformation, meaningful mathematics teaching, local culture, multicultural, cross-cultural understanding.